2010
DOI: 10.2478/v10042-010-0001-7
|View full text |Cite
|
Sign up to set email alerts
|

TGF-beta1 immunohistochemistry and promoter methylation in chronic renal failure rats treated with Uremic Clearance Granules.

Abstract: Abstract:The aim of the study was the explain the mechanism related to therapeutic effects of Uremic Clearance Granules (Niaoduqing Keli in Chinese) on adenine-induced Chronic Renal Failure in rats. Thirty 8-week-old male Wistar rats were selected and randomly divided in to 3 groups: Normal Control Group (NCG)consisted of 10 rats, Chronic Renal Failure Pathological Control Group (PCG) 10 rats, and Uremic Clearance Granules Treatment Group (UCG) 10 rats. Each rat in PCG and UCG was fed with adenine-enriched die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…In clinics in China, UCG is frequently used to treat the CRF patients, and that, it can significantly ameliorate renal dysfunction and tubulointerstitial fibrosis for CKD patients at stage III to stage IV (Meng et al, 2013a). The recent studies in vivo and in vitro preliminarily expounded that UCG could lessen tubulointerstitial fibrosis via depressing TGFbeta1 over-expression, inhibiting tubular epithelial myofibroblast transdifferentiation and retarding oxidative stress damage (Miao et al, 2010;Lu et al, 2013). Despite this, the deep therapeutic mechanisms involved in vivo are still unclear.…”
mentioning
confidence: 99%
“…In clinics in China, UCG is frequently used to treat the CRF patients, and that, it can significantly ameliorate renal dysfunction and tubulointerstitial fibrosis for CKD patients at stage III to stage IV (Meng et al, 2013a). The recent studies in vivo and in vitro preliminarily expounded that UCG could lessen tubulointerstitial fibrosis via depressing TGFbeta1 over-expression, inhibiting tubular epithelial myofibroblast transdifferentiation and retarding oxidative stress damage (Miao et al, 2010;Lu et al, 2013). Despite this, the deep therapeutic mechanisms involved in vivo are still unclear.…”
mentioning
confidence: 99%
“…37 By remethylation of TGF-beta1 promoter and then the TGF-beta1 be transcripted and translated normally, Uremic Clearance Granules (Niaoduqing Keli in Chinese) was proved to be able to reduce serum creatinine, blood urea nitrogen, and homocysteine in adenine-induced CRF rats. 38 A combination of two Chinese herbs, Astragalus membmnaceus var. mongholicus and Angelica sinensis, displayed renoprotective effects by suppression of extracellular matrix deposition, upregulation of vascular endothelial growth factor (VEGF), and reducing the loss of capillaries.…”
Section: The Role Of Tcms In the Treatment Of Crfmentioning
confidence: 99%
“…Clinical studies showed that NDQ reduced serum creatinine and blood urea nitrogen, improved renal function [6], and also alleviates CKD progression in patients with moderate-to-severe renal insu ciency e ciently [7]. In animal models, NDQ was found to reduce tubulointerstitial brosis and relieve CKD in rat, which were related with the modulation of TGF-β and erythropoietin signaling pathways [6,8,9]. However, it's still unclear that if NDQ attenuates CRF by inhibiting TGF-β1-induced EMT.…”
Section: Introductionmentioning
confidence: 99%